The Role of Self-Efficacy on Innovative Work Behavior Moderated by a Creative Climate - Siska, Depi Pran; Qodriah2, Sari Laelatul; Risdianto, Risdianto (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to investigate the influence of self-efficacy on innovative work behavior, with the creative climate serving as a moderating variable. The study was conducted among PT employees. Dok & Perkapalan Kodja Bahari (Persero) Galangan Cirebon, a sector currently facing challenges in promoting employee creativity. Insufficient self-efficacy and an inadequate creative milieu have been recognized as impediments to inventive behavior.Methods: This quantitative study employed a saturated sample of 70 employees, with data collected through questionnaires. The analysis employed Moderated Regression Analysis (MRA) to evaluate the direct impact of self-efficacy on inventive work behavior and to examine the moderating influence of creative climate. Result: The findings demonstrate that self-efficacy exerts a substantial beneficial influence on innovative work behavior. Moreover, a creative climate enhances the correlation between self-efficacy and innovative work behavior, suggesting that a supportive workplace empowers confident people to articulate novel concepts. Conclusion and Suggestion: This study emphasizes the necessity of enhancing individual psychological aspects and the organizational climate to promote innovation within the maritime sector. Keywords: Self-efficacy, Innovative work behavior, Creative climate, Maritime sector